Will Superintelligence Lead to Spiritual Enhancement? - Peters, Ted (Religions, 2022)
If we human beings are successful at enhancing our intelligence through technology, will this count as spiritual advance? No. Intelligence alone—whether what we are born with or what is superseded by artificial intelligence or intelligence amplification—has no built-in moral compass. Christian spirituality values love more highly than intelligence, because love orients us toward God, toward the welfare of the neighbor, and toward the common good. Spiritual advance would require orienting our enhanced intelligence toward loving God and neighbor with heart, mind (or intelligence), and soul.